How to sharpen our discourse on corporate sustainability and business ethics: a view from the section editors - Hockerts, Kai (Journal of business ethics, 2023)
The objective of this editorial is to help authors better understand how to contribute to discourse on corporate sustainability and business ethics. We do this in two ways. First, we clarify our expectations for publication in the "Corporate Sustainability and Business Ethics" section at the Journal of Business Ethics (JBE). As section editors at the journal, we want to make explicit the criteria we apply in our decisions to accept or reject a submission. We argue that authors should explicitly reflect upon what corporate sustainability means in the context of their research. We also stress that publishing in JBE requires an explicit central focus on ethics. We do not take a position on how authors must do either of these two, only that it should be done. In short, there are good business ethics papers that do not add to corporate sustainability theory building or practice, and there are good corporate sustainability papers that are not framed in a business ethics discourse. For the "Corporate Sustainability and Business Ethics" section, we expect authors to strive for both. Second, we provide several illustrations of how corporate sustainability research can be framed from a business ethics perspective around three central sustainability constructs: objective function, carrying capacity, and generational sustainability. These examples are not intended to be comprehensive or to bound the range of acceptable research for JBE's "Corporate Sustainability and Business Ethics" section. Rather, we aim to provide representative examples of potentially publishable research on business ethics and corporate sustainability to spur innovative thinking and constructive discussion. We hope this editorial will help authors better understand what we expect from submissions to the "Corporate Sustainability and Business Ethics" at JBE.